Preservation of Cultural Heritage Community: Cases of Thailand and Developed Countries - Supoj Prompayuk; Panayu Chairattananon (My University, 2016)
Preservations of cultural heritage community in Thailand often found that the heritage buildings and surroundings are carefully preserved while the way of life and socio-economic structure are not. On the other hand, this is not the same in developed countries. Therefore, this study aimed to investigate the method of successful cultural heritage community preservation in those states. The conclusion is that, in order to preserve this heritage successfully, the preservation method must have an establishment of organizations that effected changes and systematic management procedures for maintenance.
Keywords: Cultural Heritage Management and Preservation